Students satisfaction towards library services at Perpustakaan Tun Dr. Ismail (PTDI), UiTM Cawangan Johor, Kampus Pasir Gudang / Mohd Yusri Ab Khadi - Ab Khadi, Mohd Yusri (UiTM Cawangan Johor Kampus Pasir Gudang, 2014)
This study aimed to investigate the level of satisfaction towards library services. It also aimed to identify the types of services that students satisfy and their perceived towards the overall assessment of services at Perpustakaan Tun Dr. Ismail (PTDI), UiTM Cawangan Johor, Kampus Pasir Gudang. SERVQUAL dimension were used to investigate students satisfaction. Based on findings of this study, it shows that students satisfied with services provided by PTDI.